ANALISA KADAR ASAM URAT PADA WANITA MENOPAUSE DI DUSUN XI DESA BANDARKHALIPAH KECAMATAN PERCUT SEI TUAN - Tiara Rajagukguk; Maniur Arianto Siahaan; Erlan Aritonang (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Uric acid is the final product of purine metabolism (adenine dan guanine) and is a constituent of nucleic acids. This is the end of the biological process of the menstrual cycle decreases in esterogen levels uric acid levels in women are generally low and only increase after menopause because menopause is a point where women no longer produce esterogen, estradiol is the largest part of estradiol esterogen plays a role in helping uric acid excretion get sick through urin. The population in this study were menopausal women. Aims to determine uric acid levels in menopausal women. Research with the title analysis of uric acid levels in menopausal women in the hamlet XI village Bandar khalipah sub district percut sei master 2018.uses the easytouch brand stick tool. uses descriptive cross sectional research type. Examination of uric acid levels 20 samples of post menopausal women obrained normal uric acid levels of 11 people (55%) and uric acid is levels increased by 9 people (45%). Post menopausal women to kepp checking regulary to determine the progression of the didease